Repeated misdiagnosis of small intestine bronchogenic cyst: a case report - Chen, Xiaodong; Hu, Danfei; Gao, Wenbo; Wu, Qihang; Qin, Xiangcheng; Wang, Zhichao; Xu, Yangkai; Chen, Dong; Li, Nan; Weng, Guobin (Frontiers in Oncology, 2024)
Bronchogenic cysts are uncommon congenital malformations of the respiratory system. These cysts can be categorized as intrapulmonary, mediastinal, or ectopic. Ectopic bronchogenic cysts, which lack distinctive clinical and imaging features, are particularly challenging to diagnose. This study presents a 48-year-old woman having a small intestinal bronchogenic cyst. She was repeatedly misdiagnosed as having an ovarian chocolate cyst or a cystic mass of bladder origin three years ago. However, no cyst was found during the operation. Half a year prior to presenting at our hospital, the patient developed frequent urination, prompting her to seek further treatment. We eventually discovered a cyst in the small intestine. The histological evaluation of the specimen showed a bronchogenic cyst. Small intestine bronchogenic cysts are extremely rare and easily misdiagnosed. It should be considered as one of the differential diagnoses of pelvic cysts. Particularly, when intraoperative exploration of the pelvic cavity fails to detect any cysts, consideration should be given to the possibility of small intestine bronchogenic cysts.